The relationship between fake news and fake medicines: how misinformation has fuelled the sale of COVID-19 substandard and falsified medical products - Pyzik, Oksana; Hertig, John; Kanso, Hoda; Khan, Sofia (Journal of EAHIL, 2021)
As waves of COVID-19 continue to threaten public health, an increasing volume of disease-related information is widely accessible, and not all of it is accurate or reliable. The World Health Organisation (WHO) described this overabundance of information, misinformation, and disinformation as an "infodemic", making it difficult for many to distinguish fact from fiction. These definitions are complex and transitional; however, misinformation is defined as the "inadvertent sharing of false information", whereas disinformation is more sinister in origin and constitutes "the deliberate creation and sharing of information known to be false." The infodemic encapsulates both intentional and unintentional erroneous sources. Ultimately, the patient safety consequences remain the same, including amplifying vaccine hesitancy and propagating dangerous "coronavirus cures" myths, leading to higher COVID related mortality rates. Disinformation, desperation, and panic drive the production and sale of falsified medical products. The WHO estimates 1 in 10 medical products in low-and-middle-income countries (LMIC) settings are substandard or falsified (SF), which may worsen diseases, cause disability or even death. Ultimately, SF products undermine public trust in COVID-19 vaccines and treatments, all sectors must come together in this crisis to ensure quality covid medical products are distributed safely and fairly to end the pandemic sooner rather than later.